(untitled) (Huellas, 2023)
Josafat Morales Rubio’s book "Oil in the Mexican social imaginary. Nation, heritage and sovereignty" (2020), analyzes the symbolic appropriation of this hydrocarbon in Mexico, recovering a process that spans from the expropriation of the resource from foreign hands in 1938, up to the present. His hypothesis expresses that there is a predominant significance linked to an element that goes beyond the definition of commodity. This could be considered as such, if it occurred only within the framework of public policies for the productive development of a nation. But never It happens that way. The author makes it clear that the strong significance of oil corresponds to symbolic factors prevalent in Mexican society.